Analysis of Inquiry Learning in Elementary School Students in Science Subjects - Suharyanto H Soro; Sutisna (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to describe the inquiry abilities mastered by elementary school students when given inquiry-based activities. The research method used is descriptive qualitative which was carried out in one of the elementary schools in the city of Bandung, West Java. Data collection was carried out by giving students inquiry-based activity sheets containing seven stages of activity. Inquiry activity sheets are done by students from Class III to Class VI of Elementary School. The total number of students working on the inquiry activity sheet was 112 people. The results showed that there were five inquiry abilities that emerged and had differences in each ability from Class IV to Class VI. These five emerging inquiry abilities have developed from the number of students who master at each level and the composition of each ability. Classically, students at the Grade III level are said to have not mastered inquiry abilities.